REFLECTING TO LEARN: THE ASPECTS OF REFLECTION AS REFLECTED BY ENGLISH TEACHERS IN THEIR REFLECTIVE PRACTICE (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2018)
Reflective practice has become central issue in teacher professional development. Through reflective practice, it is expected teachers can improve their teaching quality and develop their professionalism as well. As a tool of professional development, reflective practice offers opportunities to teachers to reflect on their teaching. There are some aspects that can be included in teachers’ reflection. This qualitative case study was aimed at investigating some aspects of English teachers reflected in their reflective practice. 4 in-service English teachers were involved as respondents of the study. Data were collected through interview and documentation. Then, they were analyzed by using interactive model analysis for qualitative study. The results of data analysis were elaborated by using narration. There were four major findings emerged as the aspects of teachers’ reflection in their reflective practice; classroom management, teaching strategy, teaching and learning material, and students difficulties in learning
Keywords: reflective practice; teacher professional development; aspects of reflection